Growth and reproductive performance of Fogera cattle breed at Andassa Livestock Research Center - Tesfa, A.; Kumar, D.; Abegaz, Solomon; Mekuriaw, Getinet; Bimerew, T.; Kebede, A.; Bitew, A.; Ferede, Y.; Mazengia, H.; Tilahun, M. (2016)
The objective was to evaluate the growth and reproductive performances of Fogera cattle breed at Andassa Livestock Research Center, Ethiopia. The data covers the period from 1992 to 2013 that were collected from farm records of the center. The fixed effects were birth year, season, sex, parity, mating type and dam source. The least squares means and standard errors of birth and weaning weight were 21.4±0.09 and 102±0.77 kg, respectively; whereas age at first service, age at first calving, calving interval and number of service per consumption were 38.9±0.72 month, 51.8±0.72 month, 19.5±0.32 month and 1.17±0.01, respectively. Weaning weight and other reproductive performance traits showed slight up and down trends across the years which indicated fluctuation of management and other husbandry practices at the center. Almost all the non-genetic factors considered in the study had an effect on the production and reproductive performances of the breed.